1968
DOI: 10.1039/j39680002716
|View full text |Cite
|
Sign up to set email alerts
|

1,2:5,6-Di-O-cyclohexylidene-3-C-methyl-α-D-allofuranose and other branched-chain analogues

Abstract: The reactions of 1 ,2 : 5,6d i -0cyc I o h exy I i d e n ea -D -rib0 -3h exof u ra n 0s u I o se with met h y I mag n es i u m bromide a n d with methyl-lithium yield the same 3-C-methyl derivative ; the configuration of this compound was established by preferential hydrolytic removal of the 5.6-O-cyclohexylidene residue, oxidative removal of C-6 with periodate, and a co n s i d e r a t i o n of the pro pert i es of t h e i so I a ted prod u c t, 1 ,2 -0 -c yc I o h exy I id en e -3 -Cm e t h y I -Q -D -rib0 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, when difluoroalkenes 76a or b were reacted with hypophosphorous acid sodium salt 55b in the presence of triethylborane and air, a complete consumption of the substrates occurred and adducts 77 were isolated as a single diastereomer in each case (Scheme 17) [38]. Despite the smaller size of the reacting radical (when compared to phosphonyl and phosphonothioyl radicals), the stereodirecting effect of the 1,2-acetonide unit proved efficient in blocking the concave face of the ribofuranose [15,38]. Transforming adduct 77a into phosphite 78 and interaction with oxygen (air) or sulfur afforded protected phosphonic acid 79 and phosphonothioic acid 80, respectively, in the form of their solid, disodium salts (86% and 59% isolated yield, respectively) [39].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, when difluoroalkenes 76a or b were reacted with hypophosphorous acid sodium salt 55b in the presence of triethylborane and air, a complete consumption of the substrates occurred and adducts 77 were isolated as a single diastereomer in each case (Scheme 17) [38]. Despite the smaller size of the reacting radical (when compared to phosphonyl and phosphonothioyl radicals), the stereodirecting effect of the 1,2-acetonide unit proved efficient in blocking the concave face of the ribofuranose [15,38]. Transforming adduct 77a into phosphite 78 and interaction with oxygen (air) or sulfur afforded protected phosphonic acid 79 and phosphonothioic acid 80, respectively, in the form of their solid, disodium salts (86% and 59% isolated yield, respectively) [39].…”
Section: Resultsmentioning
confidence: 94%
“…As this last step would probably play a crucial role in installing the requisite configuration on carbon C 3 0 , it was decided to start from a furanose derivative featuring a hindered a-face to force the hydrogen quenching to occur on the b-face (thereby positioning the phosphonodifluoromethyl unit on the desired face of the cycle), and to introduce the base in a subsequent step. Glucofuranose derivative 12 was chosen as a readily available substrate, because of the 1,2-dimethyl acetal protection and the known steric hindrance generated by the angular methyl group (Scheme 2) [15]. Oxidation of the C 3 0 hydroxyl group with Dess-Martin periodinane resulted in a clean and smooth production of ketone 13, which was subjected to the action of the anion of diethyl difluoromethylphosphonate [16].…”
Section: Resultsmentioning
confidence: 99%
“…Opiates are known for their prototypical analgesic and pharmacological importance ( , ). It is observed that opiates inhibit either the basal () or neurostimulated increase in the adenylate cyclase activity in several mammals ( ) and cause respiratory depression () due to their action on the brain stem respiratory centers. Owing to their immense importance in biochemical studies, the concept of opioid receptor was first postulated by Beckett and Casy (), and subsequently, Portoghese and co-workers () proposed different opiate receptors for structurally different opioids.…”
mentioning
confidence: 99%